Seleksi 21 Galur Kecipir (Psophocarpus tetragonolobus L.) Berdasarkan Karakter Kualitas Polong yang diinginkan Konsumen - Bramastyo, Doni; Saptadi, Darmawan; Yulianah, Izmi (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2020)
Winged bean (Psophocarpus tertragonolobus L.) belongs to the Fabaceae family with many benefits (multifunctional). Winged bean pods have a lot of nutrients that are good enough for the body. The utilization of fresh winged bean pods is still very low by the community. This can be caused by several factors, one of which is the quality attributes and economic value possessed by winged bean commodities which are still relatively low when compared to other vegetables. In the agricultural industry, improving quality is very necessary because it will affect consumer decisions in choosing and buying. This study aims to determine the characteristics of the pods favored by consumers so that potential lines can be developed based on consumer preferences. The study was conducted in November 2017 to September 2018 with two methods, namely a field trial conducted in Dadaprejo Village, Junrejo District, Batu City, Malang, East Java and a market survey conducted in Malang City. Field experiments were carried out using a Randomized Block Design (RBD). Observation variables were divided into two, namely quantitative variables consisting of pod length and increased pod hardness, and qualitative variables consisting of pod shape, color, taste, and hardness. The results showed that there were lines that had the potential to be developed based on the preferences of consumers, these lines were PTL 2.1. Other lines of these lines, other lines that are close to similar potential are lines of UB 1.1, DJB 2, DJB 1, NSM 2.1 and MDM 1.2.